1982
DOI: 10.1080/00480169.1982.34915
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis: II. Investigation of clinical disease in dairy cattle in the Waikato district of New Zealand

Abstract: Investigations were carried out in 1975, 1976 and 1977 in 16 dairy herds where leptospiral abortions were suspected and in five other herds where clinical disease was not present. Both Leptospira interrogans serovars pomona and hardjo were isolated from cattle in herds with leptospirosis, but only pomona was recovered from those that had aborted. There was no evidence that hardjo caused clinical disease in dairy cattle in the Waikato district. It was found that 73% of the cows that aborted and 19% of other ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
(1 reference statement)
1
7
0
Order By: Relevance
“…antibodies was 21.4% and primarily due to serovar Hardjo (seroprevalence of 17.0%). The implication of a positive titer to serovar Hardjo on fetal loss remains controversial as many studies failed to show a causal association between seropositivity and abortion [ 22 , 45 48 ], while others described Hardjo as a cause of abortions [ 49 , 50 ]. The interpretation of the serological results for Leptospira spp.…”
Section: Discussionmentioning
confidence: 99%
“…antibodies was 21.4% and primarily due to serovar Hardjo (seroprevalence of 17.0%). The implication of a positive titer to serovar Hardjo on fetal loss remains controversial as many studies failed to show a causal association between seropositivity and abortion [ 22 , 45 48 ], while others described Hardjo as a cause of abortions [ 49 , 50 ]. The interpretation of the serological results for Leptospira spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, Leptospira shedding was also identified in subclinically infected cattle [5,7,8]. Carter et al [5] and Cordes et al [7] found 0.7% and 0.4% of dairy cows, respectively, in Waikato farms were shedding Leptospira without showing any clinical signs. The true percentage of cattle shedding Leptospira might have been higher since the detection was based on microscopy and culture techniques.…”
Section: Introductionmentioning
confidence: 99%
“…During that period, clinical leptospirosis with leptospiruria in cattle was frequently diagnosed and largely associated with Pomona infection [5,6]. However, Leptospira shedding was also identified in subclinically infected cattle [5,7,8]. Carter et al [5] and Cordes et al [7] found 0.7% and 0.4% of dairy cows, respectively, in Waikato farms were shedding Leptospira without showing any clinical signs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations